Measurement of professional identity in Chinese nursing students - Yu-Fang Hao; Hui-Jun Niu; Li-Ping Li; Shu-Jin Yue; Xiao-Hong Liu (Elsevier, 2014)
Objectives: Chinese nurses continue to display low professional identity. It is becoming an emergent issue in China how to help nurse students develop their positive professional identity. This paper is to develop the Professional Identity Scale for Nursing Students (PISNS). Methods: Literature review, and interviews with students and experts were adopted to develop initial item. Reliability and validity of the scale were respectively examined by computing internal consistency coefficient alpha and split-half Spearman Brown for equal length, and Exploratory Principle Component Factor Analysis. Results: Five factors with 17-item were obtained explaining 58.9% of the total variance. Cronbach's alpha, and split-half reliability was 0.83 and 0.84 respectively. Conclusions: Given its high reliability and validity, PISNS could be used as a measurement tool for educators to evaluate the developing level of professional identity in nursing students and assess the effectiveness of corresponding interventions and strategies.